Prevalence and Determinants of Pre-lacteal Feeding: Insights from the 2017 Indonesia Demographic and Health Survey - Nurokhmah, Siti; Masitoh, Siti; Werdani, Kusuma Estu (UI Scholars Hub, 2021)
Pre-lacteal feeding is widely known as a distraction to exclusive breastfeeding, and the malpractice continues to be prevalent in Indonesia. Therefore, this study aimed to explore the potential determinants of pre-lacteal feeding among mothers of infants below 24 months. A sample of 6,455 mother-infant pairs from the 2017 Indonesia Demographic and Health Survey (IDHS) was used. Also, multivariate logistic regression was employed to identify factors associated with pre-lacteal feeding practice. In Indonesia, 44% of infants were introduced to solid/liquid feeds in their first three days of life. Infant formula was the most common pre-lacteal feed given, followed by any other milk, plain and sugar water, and honey. Early initiation of breastfeeding and living in an urban area was protective method against pre-lacteal feeding (AOR: 0.24; 95%CI: 0.21-0.28; AOR: 0.76; 95%CI: 0.65-0.90, respectively), while cesarean delivery acted as arisk factor (AOR: 1.36; 95%CI: 1.14-1.63). Meanwhile, gender role attitude, parity, perceived birth size, and household wealth index was also associated with pre-lacteal feeding. Overall, the percentage of mothers introducing pre-lacteal feeds was still high. The modifiable covariates associated with pre-lacteal feedings, such as early initiation of breastfeeding, parity, and birth size, were the major factors discouraging this practice.